Oxidação lipídica em peixes: mecanismo de ação e prevenção - Fogaça, F. H S; Sant'ana, L. S. [UNESP] (My University, 2009)
Aquaculture produces food with high nutritive value, however its environmental conditions and management increase the stress reaction of fishes, prejudicing the quality of their products. The lipid oxidation is one of the main causes of the fishery deterioration, due the high unsaturated value of fatty acid of aquatic organisms. This review describes lipid oxidation mechanisms, their analysis methodology and some preventive ways, emphasizing the antioxidants effects of vitamin E utilization in fish's diet.
Lipid oxidation in fishes: Action mechanism and prevention
Keywords: Antioxidant; Propagation; Unsaturated fatty acids; Vitamin E; Pisces